Removal of cadmium from contaminated soil using biosurfactants produced by bacteria isolated from cadmium-contaminated cacao fields (2019)
A new regulation on the content of Cadmium (Cd) in food products derived from cocoa will be applied by the European Union from January 2020. The high content of Cd in these products is related to the high content of the metal in the grains of cacao, which in turn is related to high Cd content in the crop soils. The objective of this work was to isolate bacteria capable of producing biosurfactants from cacao soils where the Cd concentration was considerably high. These biosurfactants could be used to remove the metal from the ground. Soil samples were taken and from the three ones with the highest metal concentration an isolation of bacteria was performed. Eleven morphotypes that were tolerant to the presence of Cd were isolated and then grown in rhodamine agar to check which ones were potential biosurfactant producers, observing if they showed bioluminescence. Two morphotypes glowed under UV light. A growth of these two was performed in liquid medium and an extraction for surfactants was performed. The extraction was run in HPLC under a specialized configuration to detect rhamnolipids, the type of biosurfactants associated with metals, and a peak that is suspected to represent the presence of these compounds was observed. Finally, a greater amount of biosurfactant was extracted from the culture of the two bacteria and applied to the initial soil from which they had been extracted. New Cd measurements were done to the soil and a removal of up to 70% of the concentration was reached using the highest concentration biosurfactant. It was determined that the morphotype called C8 was more efficient in the production of biosurfactant.